Removal of Congo Red and Procion Red Using Zn/Fe Pillared Bentonite. Issue 1 (November 2021) - Desnelli,; Asri, W R; Hasanudin,; Said, M; Hariani, P L
Abstract: The process of pillarization of metal oxide Zn/Fe compounds in bentonite has been carried out. The study of adsorbent weight, pH, adsorption time, and initial concentration were investigated to get the optimum reduction of Congo red and Procion red concentration. In addition, the pseudo kinetic also determined to investigate the rate and type of adsorption. From the experiment, the optimum conditions for removal of Congo red for the adsorbent weight, pH, and adsorption time were 0.02 g, 2, 20 minutes, respectively, while for the removal of Procion red was 0.04 g, 2, 20 minutes, respectively and both of adsorbent followed the pseudo-second-order model kinetics with chemisorption mechanism. Although the optimum conditions for removal of the two dyes were similar, in fact the percentage removal of the Congo red dye was greater. In conclusion, the Zn/Fe pillared bentonite was more suitable for the removal of the Congo red than Procion red.